PENGARUH KOMITMEN KERJA DAN PENGAWASAN TERHADAP DISIPLIN PEGAWAI KANTOR CAMAT PASAR MUARA BUNGO KABUPATEN BUNGO - Muhammad Asman; Muhammad Yusup (Jurnal Manajemen Sains, 2022)
This study aims to determine the effect of work commitment and supervision on employee work discipline at the Pasar Muara Bungo Sub-district Office, Bungo Regency partially and simultaneously. The method used in this research is a quantitative approach. The sampling technique of this research is saturated sampling with a total population of 38 people, and the sample is only 37 people. The analytical tool used is multiple linear regression with the results of the study is Y = 15,729 + 0.397 (X1) + 0.270 (X2) + e. Partial and simultaneous test results show the influence of work commitment and supervision variables on employee work discipline. The R Square value is 0.801 or 80.10%. Where the dependent variable (Y) can be explained by the two independent variables of 80.1%, while the remaining 19.9% is influenced by other dimensions outside the study.